1997
DOI: 10.1080/01688639708403856
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medical risk and socioeconomic status on the rate of change in cognitive and social development for low birth weight children

Abstract: Using Hierarchical Linear Models (HLM) analysis, this study evaluated the effects of medical risk at birth and socioeconomic status (SES) on the rate of change in cognitive and social development over the first three years of life in premature children with low birth weight (LBW). Children with LBW (n = 79) with both high (HR) (n = 37) and low (LR) (n = 42) medical risk were compared to healthy full-term (FT) (n = 49) children. Children were assessed longitudinally at 6, 12, 24, and 36 months for cognitive dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…In relation to social and personal development studies, the reviewed studies found that preterm children have problems in social adjustment in the first months (35,68), in task persistence also at 4 years (35,44), in emotional regulation and social interactions from the first year of life (37,39,44,68,71), in emotional adjustment (48,68), in the development of secure attachment and social competence in the early years (5,48,71), in internalizing behavior at two years (such as shyness, fear, anxiety, depression) (5, 71) and behavioral difficulties, such as hyperactivity at 3, 5 and 6 years (76). However, there is no agreement between the studies regarding externalizing behavior problems, such as aggression, hyperactivity and defiance, or emotional expression and regulation difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to social and personal development studies, the reviewed studies found that preterm children have problems in social adjustment in the first months (35,68), in task persistence also at 4 years (35,44), in emotional regulation and social interactions from the first year of life (37,39,44,68,71), in emotional adjustment (48,68), in the development of secure attachment and social competence in the early years (5,48,71), in internalizing behavior at two years (such as shyness, fear, anxiety, depression) (5, 71) and behavioral difficulties, such as hyperactivity at 3, 5 and 6 years (76). However, there is no agreement between the studies regarding externalizing behavior problems, such as aggression, hyperactivity and defiance, or emotional expression and regulation difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Landry et al (39) found that preterm children were less initiating in social interactions than their full-term peers between 2 and 4.5 years of age. Landry et al (75) also found that at 4.5 years, preterm children differed in their levels of play and social initiating skills from full-term children, who engaged in more pretend play and needed fewer trials to succeed in tasks.…”
Section: Personal and Social Development Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth modeling may be a particularly valuable means of determining whether children who show different rates of development show different patterns of relations between specific early parenting behaviors and growth in social and cognitive processes. Very low birth weight (VLBW) infants of varying degrees of early medical risk are one group who may require more specialized parenting to optimize their development because, as a group, they show slower rates of growth in cognitive and social skills through 3 years of age as compared with FT infants (Landry, Denson, & Swank, 1997). Whereas growth appears slower for VLBW infants as a group, as within any group, there are individual differences in this growth suggesting that some children, will show faster rates of gains than will others (Landry et al, 1997).…”
mentioning
confidence: 99%
“…Normal birth weight controls are often not included when comparing the outcome of lowrisk versus high-risk birth weight groups, eg, in studies assessing the effects of chronic lung disease, brain hemorrhage, jaundice, etc. 149 In contrast to school-age studies, descriptive studies of early-childhood outcomes of high-risk children (Ͻ3 years) have often not included control subjects. However, it is currently recommended that if the true impact of prematurity is to be identified, "normal" control populations should be included at all ages.…”
Section: Objective 4: Determine the Relevant Issues Related To Selectmentioning
confidence: 99%